Effect of 4 wk of deep water run training on running performance - Bushman, B. A.; Flynn, M. G.; Andres F. F.; Lambert, C. P.; Taylor, M. S.; Braun, W. A (Medicine & Science in Sports & Exercise, 1997)
Whether trained competitive runners could maintain on-land-running performance using 4 weeks of deep water run training instead of on-land training was investigated. Well-trained competitive runners (M = 10; F = 1), trained exclusively using deep water run training for 4 wk. Ss trained 5-6 days per week for a total of 20-24 sessions. Instruction and practice sessions were conducted prior to the training period. Before and after the deep water run training, Ss completed a 5-km race on the treadmill using a computer based system, a submaximal run at the same absolute workload to assess running economy, and a combined lactate threshold and maximal oxygen consumption test. No significant differences were found for 5 km run time, submaximal oxygen consumption, lactate threshold running velocity, or maximal oxygen consumption. Also no differences were found among Global Mood State pre-training, each week during training, and post-training. Competitive distance runners maintained treadmill running performance using 4 weeks of deep water run training as a replacement for on-land training. It is possible that the treadmill running task was not reflective of the specific qualities of ground running and therefore is a measure that is independent of the specific nature of ground running. If this is the case, then it does not reflect the idiosyncrasies of specific running and should not be expected to change as a result of other unrelated (deep-water) training. Implication: Well-trained runners were able to maintain trained running performances by running in deep water. This would support "cross-training" of this nature but needs to be replicated before it is accepted as supporting cross-training in light of the overwhelming evidence that supports the principle of specificity. The nature of measures of training in this study may not have produced a valid evaluation of the hypothesis that was tendered.